Participatory digital transformation model for MSME financial reporting: integrating PRA and TELOS through SIAPIK in developing economies - Ayu Sartika Pane; Puteri Ayu Pratiwi (Jurnal Mantik, 2026)
The limited adoption of standardized financial reporting among micro, small, and medium enterprises (MSMEs) persists despite the availability of digital accounting tools. Existing studies predominantly focus on technological aspects, while overlooking the gap between system availability and actual user adoption, particularly in micro-scale, craft-based enterprises. This study addresses this gap by examining the role of participatory approaches in facilitating digital financial reporting practices. This research aims to develop and evaluate a participatory digital transformation model by integrating Participatory Rural Appraisal (PRA) and the TELOS feasibility framework in the implementation of the SIAPIK application for MSMEs. A qualitative case study was conducted involving five key stakeholders selected through purposive sampling. Data were collected through in-depth interviews, focus group discussions, and document analysis, and analyzed using thematic coding and triangulation. The findings indicate that MSMEs rely on informal financial practices, including incomplete transaction records and estimation-based decision-making. The application of PRA enhances user engagement and supports the transition from manual to digital bookkeeping. The TELOS analysis shows that while SIAPIK is technically and economically feasible, its effective use depends on continuous mentoring and contextual adaptation. This study contributes by proposing an integrated participatory digital transformation model, highlighting that successful adoption of digital financial systems requires not only technology, but also user-centered facilitation mechanisms.